The Impacts of the COVID-19 Pandemic on Mental Health across Different Genders and Sexualities - Jiale Zhu; Jonas Katona (Undergraduate Research Journal for the Human Sciences, 2023)
Current studies report an increase in psychological distress as a result of the COVID-19 pandemic. This study is interested in examining mental health disparities and how the COVID-19 pandemic has disproportionately impacted marginalized groups—and more specifically, those identified by sex, gender, and sexuality—compared with the general population. This study also considers the effects and ramifications of different policy measures taken during the course of the pandemic. We perform exploratory data modeling and analysis on several important and publicly available datasets taken during the pandemic on mental health and COVID-19 infection data across various identity groups to look for significant disparities, correlations, and causations across different times and identities. This paper uses these analyses to suggest policy measures that could improve public wellness during future public health crises, and in particular across different identities.
Keywords: COVID-19; Mental Health; Gender Disparity; Public Health Policy; Vaccination; Data Modeling